Precision surface irrigation with conjunctive water use - Anwar, Arif A.; Ahmad, W. (Springer, 2020)
The Indus Basin Irrigation System is characterized as a gravity surface irrigation system, with minimal on-line or off-line storage and limited distribution control. An important characteristic is the limited water availability. On field irrigation within the Indus Basin Irrigation System is almost entirely using surface irrigation and only very few farms adopting pressurized irrigation systems. The objective of the warabandi management system that characterizes the Indus Basin Irrigation System is to distribute the limited available water as equitably as possible. This research evaluates surface irrigation under furrow and border strip irrigation using canal water and groundwater conjunctively. This paper presents results from a numerical model and field observations, to examine the precision surface irrigation paradigm within the water supply constraints imposed by the warabandi system of the Indus Basin Irrigation System. We conclude that laser grading within the IBIS is achievable at a modest cost and effort. Our findings suggest that the improved laser-graded profile persists for at least three crop seasons. Furrow irrigation can attain a high performance using either available canal or groundwater with low quarter distribution uniformity and low quarter application efficiency as performance indicators. Border irrigation can also attain a high performance provided irrigation is changed to fortnightly. Model predictions of advance curve and low quarter distribution uniformity are compared to field observations and in-situ measurement.